Aplikasi Penyewaan Alat Laboratorium Fakultas Perikanan dan Ilmu Kelautan Universitas Papua - Sanglise, Marlinda (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2019)
The Faculty of Fisheries and Marine Sciences (FPIK) is one of the Faculties at the University of Papua which has two majors namely, Aquatic Resources and Marine Sciences. Each department has a laboratory that can be rented by students, lecturers, and the general public. The large number of laboratory equipment often makes it difficult for laboratory managers to arrange loan data and return laboratory equipment. Most of the borrowing data is filed in the form of files which might be damaged if a disaster occurs, besides that the means to promote laboratory equipment rental services for the general public are still manual, by placing advertisements placed on the FPIK Walls, which are generally can be seen by students in the Faculty. Based on this condition, an application for leasing laboratory equipment was made in FPIK using Macromedia Dreamweaver 8 and PHP Mysql. With the existence of this application it can help each process of borrowing and returning laboratory equipment more effectively. Some features contained in this application include member registration, registration of loan forms, return forms, tool data, and transaction lists.